Recovery of Functional Independence After Traumatic Transtentorial Herniation With Duret Hemorrhages - Edlow, Brian L.; Threlkeld, Zachary D.; Fehnel, Katie P.; Bodien, Yelena G. (Frontiers in Neurology, 2019)
Historically, Duret hemorrhages have conferred a devastating prognosis. However, recent case reports suggest that cognitive and functional recovery are possible after Duret hemorrhages. Here, we describe a patient who recovered consciousness, communication, and functional independence after Duret hemorrhages caused by traumatic transtentorial herniation. We performed prospective, standardized behavioral assessments, structural MRI scans and stimulus-based functional MRI (fMRI) scans during the first 2 years of recovery. The multimodal assessments revealed reintegration of neural networks mediating language and consciousness, concurrent with the reemergence of functional independence. These observations provide insights into network-based mechanisms of recovery from coma and add to a growing body of evidence indicating that Duret hemorrhages are not invariably associated with a poor prognosis.